MINAT BERWIRAUSAHA MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN JURUSAN PENDIDIKAN TEKNIK SIPIL FPTK UPI - GUMILAR, Anggi (2012)
Being a businessman is an alternative choice. At least, with entrepreneurship means providing employment for themselves do not need to depend on others and if their business moving forward will open up job opportunities for others. The campus is a source of science and technology and to make the campus as a place to forge themselves and their skills. Campus provides opportunities to master the science to support the business. Starting from the idea of researchers interested in conducting research with the title "Student Interests Entrepreneurship Education Program FTPK UPI JPTS Building Techniques". Research objectives were to obtain information about the high interest in entrepreneurship which is owned by the students of Technical Education Building JPTS FPTK UPI. The study population is a student of the Faculty of Education Education Building Engineering Technology and Vocational Education Indonsesia University class of 2007 and 2008 with the number of 120 students. Samples taken by proportional random sampling of the population and as many as 120 students were taken 50% or 60 students as the sample. The variables of this study is student interest in entrepreneurship Program Technical Education Building JPTS FTPK UPI. Data captured through questionnaire method. The data obtained were analyzed using descriptive analysis of the percentage.